CIBERDESIGN, O CRIATIVO DA ERA TECNOLÓGICA - FERREIRA FILHO, SEVERINO RAMOS (2017)
The work addresses, through a bibliographical research, the emergence of the professional of creation of the digital age, for that was analyzed the Eclectic that was the first advertising agency of Brazil in 1918 and the beginning of the creation double in 1950 with the inauguration of the ALMAP, but after the Internet new business models emerged, Google started a new way of advertising, created the iPhone with multitouch screen, triggering the emergence of the most diverse models of smartphones among other devices, with that the effects of mobile technology , could be felt in communication, human behavior and society. And in this new scenario of different screens and resolutions, the old static layouts of the sites were replaced by fluid layouts, the interface came to be seen as art, and it happens the appearance of Ciberdesign that is the reconsidered design in the light of virtual reality, UI Design or User Interface Design, responsible for the operation of the site and UX Design or Design of User Experiences, responsible for user experiences.